Calculations Using Rubu' Mujayyab to Determine the Beginning of Maghrib and Isha Times - Hidayat, Muhammad; Abidin, Ahmad Zainal; Fathi, Muhammad Alya; Khair, Alfath (JMEA : Journal of Mathematics Education and Application, 2024)
In determining the start of prayer times, in this case the Maghrib and Isha prayer times, there are several methods that can be used, one of which is using instruments. Apart from calculators and computers, the astronomical instrument that can be used is the Rubu' Mujayyab, which functions as an angle calculating tool. Rubu' Mujayyab is a tool in the shape of a quarter circle which is used to calculate geometric functions which are very useful for projecting the circulation of celestial bodies on a vertical circle. The research methods used are experimentation and direct testing. The results of this research show that Rubu' Al-Mujayyab can calculate prayer times, especially Maghrib and Isha times, using the steps described and the results are close to current modern calculations.